2015
DOI: 10.1002/anie.201412293
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillar Track Complexes in Template‐Directed Synthesis and Correlated Molecular Motion

Abstract: Small alterations to the structure of a star-shaped template totally change its mode of operation. The hexapyridyl template directs the conversion of a porphyrin dimer to the cyclic hexamer, but deleting one pyridine site changes the product to the cyclic decamer, while deleting two binding sites changes the product to the cyclic octamer. This surprising switch in selectivity is explained by the formation of 2:1 caterpillar track complexes, in which two template wheels bind inside the nanoring. Caterpillar tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 40 publications
4
89
0
5
Order By: Relevance
“…18,19 Since the precursor to c -P10 Cu2 is a linear pentamer containing one copper porphyrin as the central unit, the two copper porphyrin units in the ten-membered ring will necessarily be sitting opposite each other, separated by four zinc porphyrin units on either side. The positions of the copper centers in the free ring are therefore well defined.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Since the precursor to c -P10 Cu2 is a linear pentamer containing one copper porphyrin as the central unit, the two copper porphyrin units in the ten-membered ring will necessarily be sitting opposite each other, separated by four zinc porphyrin units on either side. The positions of the copper centers in the free ring are therefore well defined.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the operation mode of the classical templating method could be totally changed only by small alterations to the structure of a star-shaped template. 31 As shown in their previous reports, the regular D 6h hexapyridyl template 11 directs the conversion of porphyrin dimer 10 to the cyclic hexamer 9 (Scheme 3). However, deleting one pyridine site of 11 changes the main product to the cyclic decamer 42, while deleting two adjacent pyridine binding sites changes the main product to the cyclic octamer Other templating methods have been developed for the synthesis of more complicated porphyrin nanorings.…”
Section: Scheme 11mentioning
confidence: 66%
“…Darüber hinaus ermöglichte ein Ansatz mit Lochmaske den Austausch von Magnesiumzentren durch andere Metalle und ebnete damit einen neuen Weg zu heterometallischen Porphyrin‐Nanostrukturen . Nach Entfernung der Template boten Andersons Porphyrin‐Nanoringe im Allgemeinen eine interessante Plattform zur Untersuchung der Thermodynamik und Kinetik von multivalenter Gastbindung …”
Section: Wirt‐gast‐chemieunclassified